Improving Documentation of Physical Health Plans After Patient Visits From General Hospital - Shehroz Shakeel (BJPsych Open, 2025)
Aims: Patients in acute psychiatric wards often require physical health assessments at associated medical hospitals. At Quinton Ward, Caludon Centre, we frequently transfer patients to University Hospital Coventry and Warwickshire (UHCW) for physical health concerns. However, their discharge plans are often not documented on CareNotes upon their return, leading to gaps in continuity of care. This audit aimed to assess whether discharge plans were documented and identify areas for improvement.